Doing Vernacularization of Ideas: The First Population/Family Planning Policy - Paredes Guillen, Lizeth Valeria (2021)
The agenda-setting and adoption of a social policy are not simple processes, they do not just require the decision of the policy-makers, they do need social participation. This article is about the first population\family planning policy in Peru, adopted in 1985 during the restoration of the democratic rule under Fernando Belaunde. Previously, we analyse the initial political process under two military regimes: Juan Velasco, who had an anti imperialist but pro-natal policy, and Francisco Morales-Bermudez, who opened the agenda on family planning. Within this political context, Belaunde allowed the participation of the social actors to create the first family planning policy. In contrast to previous literature about these governments, which focused mainly on hard policy issues, we compare a soft policy, but central element to the nation: the policy of population. In addition, as this policy concerns demographic, moral, health, and individual liberty issues, this helps us explain the role of the Peruvian State in relation to the social actors (Such as religious sectors and feminist activists), We do emphasize on the key role of the social actors, with different level of importance in its centrality at the moment of coordinating with the State.